Quality Improvement of Used Cooking Oil by Using Nanocellulose from Sugarcane Bagasse as Adsorbent - Winda Trisna Wulandari; Rosmaya Dewi (Universitas Jenderal Soedirman, 2019)
Frying oil can produce substances that are harmful for health. One way that can be used to eliminate these dangerous compounds is by using adsorbent. Recently, many adsorbents from natural fibers have been developed. One of them is cellulose which contains 40-50 % in bagasse. Nano sized cellulose or called by nanocellulose is reported have better properties than cellulose. So, this research is aimed to utilize nanocellulose from sugarcane bagasse as adsorbent for used cooking oil. Cellulose produced from bagasse is hydrolyzed using 50% H2SO4at 40 ⁰C for 10 minutes. Used cooking oil soaked with nanocellulose for 1x24 hour, 2x24 hours and 3x24 hours. Then, the quality of used cooking oil was tested through organoleptic, acid number, peroxide number and water content test. Nanocellulose produced from hydrolysis process by using acid has a particle size distribution in nanometer range, with 95.3% having a particle size of 437.5 nm. Immersion of cooking oil by nanocellulose for 2 x 24 hours can reduce the value of free fatty acids until 18.01%, the peroxide number decreases by 57.69% and the water content decreases to 99.99% even though organoleptic changes are not very noticeable. Based on this results, nanocellulose has high potential to be used as adsorbent in used cooking oil.